Нові знахідки предметів середньовічного озброєння з Рухотинського городища (уроч. Корнешти) - Калініченко, Віталій; Пивоваров, Сергій; Ільків, Микола (Київ, Інститут історії України НАН України, 2016)
The article analyzes the objects of medieval weapons found during the research of Ruhotyn hillfort (Korneshty). These include items like weapons near and distant battle and outfit details rider and horse. Melee weapons represented an ax, sabers parts, including the pommel handle and sword chapes elements bladed weapons. The items ranged weapons are arrowheads and quivers details. The protective gear is presented fragment mail (armour). The authors carried out a detailed analysis and classification discoveries. Discovered material can get important information from the military and political history of the medieval population in the Middle Dniester certain aspects of military affairs in general.
New findings of medieval weapons in the Ruhotyn Hillfort (Korneshty, Ukraine)
Keywords: археологічні дослідження; Буковина; озброєння; наконечники стріл; навершя; середньовіччя; Рухотинське городище